FEATURES OF LOGIC DEVELOPMENT IN THE EARLY OF THE XX AND XXI CENTURIES - Komakha, Larysa; Kolotilova, Natalia (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. The relevance of the study of the peculiarities of the development of the logic of the early XX and XXI centuries is due to the basic shifts within this science, which led to the majestic setof modern logic. The aim and tasks of the study areto compare the trends of logic in the early XX and XXI centuries to have the deep philosophical understanding of logic specifics as a field of scientific knowledge and academic discipline. Research methods sarehistorical and comparative methods, as well as generalization and arrangement as techniquesof scientific knowledge. Research results. It was reviewed the definition of logic as science in the works of G. Frege, J. Hintikka, J. Łukasiewicz, B. Russell, G.H. von Wright, and others, which led to the flourishing of formal logic in the XX century; the critique of formal logic in the new rhetoric; the incipience of informal logic in response to educational demands. Discussion. The issue of the subject of logic, the interconnectionbetween formal and informal logic is being actively discussed both in the domestic logical and philosophical thought (Y. Shramko, O. Shcherbyna, and others), and recognized by experts in the field of logic and argumentation theory (F.H. van Eemeren, D. Gabbay, L. Groarke and others). Conclusions. The beginning of the last century was characterized by significant shifts in logic, primarily in the scientific perspective due to the development of formal calculi and a close connection with mathematics. At the beginning of the present century, the development of logic was stimulated primarily by the demands of education, which in the second half of the XX century led to a critique of formal logic and the development of informal logic. Currently, formal and informal logics combine their efforts in the development of argumentative issues both in the direction of constructing a general theory and in the study of argumentation in different types of discourses, as well as within computer science